Система управління освітлення приміщення на базі ATmega 168P зі світлодіодною стрічкою - Пасічник, К. Ю. (ХНУРЕ, 2020)
The address LED (light emitting diode) strip is a strip of address diodes. One such strip consists of three RGB (red, green, blue) diodes and a controller. Thus, each LED has already a controller with three transistor outputs. Microcontroller based devices whose principle is to change the color of each LED individually are used to smoothly control the brightness and color of the LED strip. The address LED strip is directly connected to the Arduino Nano Atmega 168P module. With this structure, it is possible to control the color of any of the LEDs in the tape and create stunning effects.
Keywords: LED стрічка; Arduino Nano ATmega 168P; світлодіодна стрічка